CORRELATION BETWEEN KNOWLEDGE OF CITY OF RESIDENCE AND COVID19 IN SURABAYA YOUTH GENERATION - Ricky Indra Alfaray; Lionardy Yodianto; Astri Dewayani; Kartika Afrida Fauzia; Dwiki Noni Armyta; Yudith Annisa Ayu Rezkitha; Reny I'tishom; Muhammad Miftahussurur (Jurnal Layanan Masyarakat (Journal of Public Services), 2021)
COVID19 pandemic became the primer focus of health problem by the government since the case was increasing every month in 2020. The impact of this pandemic was spread quickly across many areas including Surabaya city. Youth generation often found to be a silent source of infection. Furthermore, young people behavior often ignoring health prevention policy makes the infection more easily to spread. This condition might be because of their knowledge regarding COVID19 was relatively not enough. Factor that may affect their knowledge are varies including knowledge of city of residence. This study aims to evaluate the correlation between knowledge about city of residence with youth generation knowledge of COVID19 as this factor has not yet been studied before in Indonesia. We conducted an analytical cross-sectional with an online survey for youth generation across Surabaya to understand their knowledge concerning Surabaya and COVID19. A total of 57 participants were voluntarily enrolled in this study. The result data were analyzed statistically. There is significant positive correlation between participants’ knowledge of Surabaya city with knowledge of COVID19 (r= 0.314; p= 0.017). Furthermore, knowledge of COVID19 was significantly different between youth who have better knowledge of Surabaya than lower knowledge (p= 0.021). Knowledge of Surabaya city was correlated with knowledge of COVID19. Youth who have better knowledge regarding their city of residence seem to have better knowledge of COVID19.  Knowledge concerning city of residence proven to be important in order to increase knowledge of COVID19 in youth generation.